Exploring the potential mechanism of Xiaojin Pill therapy for benign prostatic hyperplasia through metabolomics and gut microbiota analysis - Yang, Yuying; Quan, Yunyun; Liu, Yunteng; Yang, Juhua; Chen, Keyu; You, Xiaozhou; Hua, Hua; Yan, Liangchun; Zhao, Junning; Wang, Jianbo (Frontiers in Microbiology, 2024)
Background: Xiaojin Pill (XJP) is a traditional Chinese medicine prescription that can be used to treat benign prostatic hyperplasia (BPH). It has been proven to have multiple effects such as regulating sex hormone levels, anti-tumor, anti-inflammatory, analgesic, anti-platelet aggregation, and improving immunity. However, the material basis of XJP's therapeutic effect on BPH and its metabolic process in vivo remain to be clarified. At the same time, many microorganisms that exist in the urogenital tract, including those related to BPH, can also affect the host's health. Results: XJP contains 91 compounds that alleviate BPH rat pathologies, decreasing prostate weight, index, and serum DHT, PSA, EGF, bFGF, VEGF levels. It inhibits prostatic epithelial cell apoptosis and downregulates Bax, TGF-β1, IGF-1 proteins in the caspase-3 pathway. Metabolomics studies reveal 10 upregulated and 10 downregulated metabolites in treated rats, with 5-Methylcytosine, Uracil, and Cytosine enriched in pyrimidine metabolism. L-Arginine plays a pivotal role in metabolic pathways encompassing pyrimidine metabolism, arginine biosynthesis, and the mTOR signaling pathway. 16S rRNA sequencing uncovered that XJP optimizes the diversity and balance of intestinal flora in BPH rats by decreasing the B/F ratio, enhancing the presence of beneficial bacteria like Eggerthellaceae, Anaerovoracaceae, and Romboutsia, while suppressing dysfunctional bacteria such as Atopobiaceae, Prevotellaceae_NK3B31_group, Dorea, and Frisingicoccus. Spearman analysis revealed Lactobacillus to be most associated with serum factors, whereas Romboutsia displayed the highest correlation with metabolites. This suggests that XJP modulates pyrimidine metabolism disorders in BPH rats, a regulation that aligns closely with Romboutsia, Prevotellaceae_NK3B31_group, Lactobacillus, Chujaibacter, and Enterorhabdus, thereby imparting valuable biological insights. Conclusion: In summary, these findings indicate that XJP possesses a synergistic anti-BHP effect through its multi-component, multi-target, multi-gut microbiota, and multi-metabolic pathway properties. This involves the regulation of sex hormone levels, growth factors, and the anti-epithelial cell apoptosis process. The modulation of specific gut microbiota by the host and the involvement of multiple metabolic pathways are likely one of the significant mechanisms of XJP in treating BPH. Notably, pyrimidine metabolism and the intestinal microbial ecosystem are closely intertwined in this process.